Ammonium Polyphosphate Intercalated Yttrium-Doped Layered Double Hydroxides to Enhance the Thermal Stability and Flame Retardancy of Poly(Lactic Acid) - Yufei Dai; Hongzhang Cao; Xiaoli Yu; Dequan Han; Huhu Tian; Liying Guo; Xiaodong Zhou (Advances in Polymer Technology)
The flammability of the biodegradable plastic PLA limits its application in industrial fields with high flame-retardant requirements. This paper provides a novel strategy for constructing refractory and thermostable PLA composites using layered double hydroxides (LDHs) chemically modified with ammonium polyphosphate (APP). XRD, FT-IR, SEM-EDS, and TEM confirm that the goal of LDHs has been successfully prepared. The thermal stability and combustion behavior of PLA composites were evaluated by the thermogravimetric analysis (TGA) and cone calorimetry tests (CCT). The crystallization behavior and tensile performances were also examined. The results showed that the incorporation of 15 wt% MgAlY-APP-LDHs practically makes the PLA composites reach the UL-94 V-0 grade. There were 43% and 20% reduction in the PHRR and THR of PLA/15APP-LDHs respectively due to the catalytic effect of Y elements and barrier effects of LDHs, which was a major performance against fire hazards. Furthermore, the increase in crystallinity and the decrease in mechanical strength of PLA composites are attributed to the nucleation of LDHs. In short, this research introduces the production of multifunctional PLA composites through APP intercalation of LDHs, which are deemed as prospective candidates for the next generation of sustainable plastics products.